Racist Caricatures in Iceland in the Early 20th Century - Loftsdóttir, Kristín (Presses de l'Université du Québec, 2011)
In this article, the author takes the republication of the book Tíu litlir negrastrákar (hereafter Ten Little Negroes) in Iceland as an example of how Iceland is often exempted from the global heritage of racism. As scholars have started to explore relatively recently, the Nordic tends to have a hegemonic position as existing separate from colonialism of the 19th and early 20th centuries. The original publication of the book Ten Little Negroes in 1922 shows, however, the familiarity of racial caricatures in Iceland, especially when contextualized within images of Africa in general during the late 19th and early 20th centuries. In my discussion, the author places the book within the global heritage of racism, as well as discussing its connection to the more localized and national heritage of Icelandic identity, seeing the book as linking the past and the present in an interesting way.